Work Stress Management in Constructions Industry and the Contractors’ Commitment Level with the Labor Law - Al-Juboori, Salloom, A.; Alazemi, Mohammad K. (European Scientific Journal, ESJ, 2017)
Stress was defined as the challenges that excites and weaken the individual, these challenges, when removed, most people’s lives will become easier. The methodology of this work was based on two types of collecting data methods; the qualitative and quantitative. Qualitative method was based on conducting a critical literature review and investigating case studies related to the main reasons of work stress. While the quantitative method was based on collecting and analyzing data obtained from distributing 450 questionnaires to the employees in a private construction company as a casestudy. The results of the data analysis showed that the stress’s effect has many consequences on employee such as: low job involvement, a lack of interest for the organization, low performance (quality and quantity), a loss of creativity and responsibility, accident prone behavior as well as voluntary turnover. Also, the results have showed that the stress reduces the performance of workers and also decreases the quality of service by 33.9%, adversely impact on health of employees by 42.2%. Also, the stress leads to lack of the employees’ interest of the organization and reduces their affiliation to it by 66%. Finally the results illustrated that the rate of the contractor’s commitment to the texts of the Kuwaiti Labor Law was 68% as well the contractors are fair and give the employees their specified rights in the Kuwaiti Labor Law by 42.6%.